Pemahaman dan Respon Santri Persantren Terhadap Perbankan Syariah di Ponorogo - Atik Abidah (Justicia Islamica, 2013)
In 1991, the public was introduced to the establishment of shari'ah banking in conducting financial transactions. Given that the majority of Indonesia's population is Muslim, the establishment of this shariah bank has an impact on the choice of the Muslim community, which seems to be mostly still doing business in conventional banks. This is also evident in the santri community of boarding schools in Ponorogo, which still use conventional bank services. Therefore, it is interesting to see how the santri respond to this phenomenon.The method used is a questionnaire method to the students to determine theThe method used is the questionnaire method to the santri to find out the response of the Ponorogoro santri to sharia banking.The results of this study indicate that their response to the majority of sharia banks is positive. The results of this study indicate that their response to sharia banks is mostly positive. They argue that saving in sharia banks is safe and in accordance with sharia, but some of them still use conventional bank services due to lack of information and facilities provided by sharia banks.